What’s Good in the Neighbourhood? Examining the Short Run Wellbeing Impacts of Urban Regeneration Using Administrative Data - Kirkpatrick, Linda (Auckland University of Technology, 2025)
New Zealand (NZ) faces substantial housing challenges including persistent housing shortages, rising housing costs, poor quality stock and overcrowding issues. Kāinga Ora is the primary government agency responsible for social housing and urban development in NZ. Since 2018, Kāinga Ora has built nearly 10,000 new homes, most of these being social housing, and plans to further increase the housing supply by 35,000 homes over the next 15 years. By developing or regenerating urban areas (“urban regeneration”) that people live in, there is the potential to improve health and wider social outcomes in affected communities. However, given the substantial monetary investment into urban regeneration, there is little empirical evidence on the impact of urban regeneration on the wellbeing of affected communities and individuals in New Zealand. There is potential to use “big data” to derive data-driven evidence that supports Kāinga Ora’s aim to enhance wellbeing through its housing-led initiatives. This research evaluates the wellbeing impacts of urban regeneration using administrative data to assess the social return-on-investment of Kāinga Ora-led urban development. The Wellbeing Outcomes Framework developed in this study is guided by the NZ Treasury Living Standards Framework and the NZ Index of Multiple Deprivation. It is designed to measure population-wide wellbeing indicators using administrative data from Stats NZ’s Integrated Data Infrastructure across three domains: (1) human capital – education and labour market; (2) physical and mental health and (3) crime and safety. Detailed housing intensification data from Kāinga Ora is used to measure urban regeneration in Auckland, New Zealand. The empirical strategy uses staggered difference-in-differences methods to causally estimate the impact of urban regeneration on wellbeing outcomes for residents living in regenerated areas, relative to those living in non-regenerated areas between 2018 to 2021. The results broadly show no impact of urban regeneration on area-level wellbeing outcomes in the short run. While most outcomes were insignificant, there are stronger impacts found for residents living in high urban regeneration areas and social housing residents. Where significant, the impact of urban regeneration on health is mixed while the impact on crime is negative. As urban regeneration is still ongoing at the end of the analysis period, the short run impacts likely reflect negative impacts of ongoing disruption and possible displacement of residents during urban regeneration. However, these results serve as a useful starting point for policymakers to understand how individuals and communities are impacted by large housing-led policies that is guided by an empirical evidence base. Future analysis is needed to examine longer term impacts of urban regeneration once developments are complete. The Wellbeing Outcomes Framework developed in this study means longer-term wellbeing impacts of urban regeneration can be readily examined once more time has elapsed.